Nicotine without smoke—putting electronic cigarettes in context. (27th April 2016) - Britton, John; Arnott, Deborah; McNeill, Ann; Hopkinson, Nicholas; ,
Abstract : John Britton and colleagues set out why a new Royal College of Physicians report supports the role of electronic cigarettes as part of a comprehensive tobacco control strategy